Surface Roughed and Pt-Rich Bimetallic Electrocatalysts for Hydrogen Evolution Reaction - Wang, Fang; Yu, Haifeng; Feng, Ting; Zhao, Dan; Piao, Jinhua; Lei, Jianfei (Frontiers in Chemistry, 2020)
Platinum based alloys with low cost transition metals have been considered as promising electrocatalysts in the field of sustainable energy conversion and storage. Herein, chloroplatinic acid, cobalt chloride and carbon nanotubes were used as platinum, cobalt precursors and carriers, respectively, to prepare rich Pt dealloying PtCo nanoparticles (SD-PtCo/CNT) via co-liquid phase reduction and chemical dealloying method. The characterization and test results confirmed that PtCo alloy nanoparticles were evenly dispersed on carbon nanotubes, further dealloying resulting in the partially dissolving of cobalt, simultaneously generating a rich Pt layer and roughly active surface. Benefiting from the unique structure, the SD-PtCo/CNT catalyst displayed obviously enhanced HER activity in both acidic and alkaline conditions that beyond commercial Pt/C. In 1.0 M KOH, SD-PtCo/CNT exhibited a low overpotential of 78 mV at 10 mA/cm2 and small Tafel slope (38.28 mV/dec). In 0.5 M H2SO4, SD-PtCo/CNT still showed the superior performance which compared with un-dealloying PtCo/CNT, the overpotential was 17 mV at 10 mA/cm2 and corresponding Tafel slope was 21.35 mV/dec. The high HER activity of SD-PtCo/CNT can be attributed to the formation of platinum rich layer and the uniformly dispersed PtCo nanoparticles supported on superior conductive carbon nanotubes, suggesting its great potential for hydrogen generation via water splitting.